Behavior of partial and complete monolayers of argon deposited on graphite - Flenner, Elijah Jude, author; Etters, Richard D., advisor (Colorado State University. Libraries, 2003)
This calculation examines the behavior of argon deposited on graphite for various densities in the temperature range of 30K and 90K. The densities studied were 0.39, 0.71, 1.00, 1.07, 1.14, 1.22, and 1.31 where a density of one corresponds to 0.0636 atoms/Å2. For densities of 1.00 and below, two peaks were observed in the specific heat. A narrow peak around 47.3K and a broad peak around 50K. The narrow peak is identified with a rotational transition, and the broad peak is due to the melting transition, which corresponds to the loss of six fold bond orientational order. For densities of 1.07 and greater there is only one peak in the specific heat which is associated with the melting transition. Also, the motion of the atoms perpendicular to the substrate is determined to be an important aspect of the melting of complete monolayers.
Keywords: condensation; condensed matter physics